Analisis Penerimaan Teknologi Layanan Distribusi Hyperlokal Menggunakan Model TAM pada PT Inspirasi Bisnis Nusantara - Tiara Ananda Faradia; Anita, Anita; Arief Nurdini; Ardhy Lazuardy (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The rapid pace of urbanization has intensified competition among businesses, prompting the adoption of innovative strategies to enhance sales performance and customer engagement. PT Inspirasi Bisnis Nusantara, under the HAUS! brand, introduced “Huling,” a hyperlocal distribution service utilizing electric bikes (e-bikes) equipped with integrated storage boxes to improve delivery efficiency and environmental sustainability. This study aims to evaluate customer acceptance of the Huling service by applying the Technology Acceptance Model (TAM). The model incorporates five core variables: Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Towards Usage (ATU), Behavioral Intention (BI), and Actual Usage (AU). A quantitative research approach was employed, collecting data from 258 respondents through structured questionnaires. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to assess the relationships among the TAM variables. The findings reveal that PEOU has a significant positive effect on both PU and ATU, indicating that ease of use not only improves perceptions of usefulness but also fosters favorable attitudes toward adoption. PU significantly influences ATU and BI, suggesting that perceived benefits drive both positive attitudes and intentions to use the service. Furthermore, BI has a direct and significant effect on AU, confirming that stronger behavioral intentions translate into actual utilization. The analysis highlights the strongest impact along the pathway PEOU → ATU → BI → AU, underscoring the critical role of user-friendly design and positive attitudes in driving customer adoption. This research contributes to the literature by demonstrating the applicability of TAM in the hyperlocal distribution sector, offering practical implications for service providers seeking to enhance user acceptance through improved usability and perceived value. The findings suggest that optimizing ease of use and communicating tangible benefits can significantly increase customer engagement and sustained usage of innovative delivery services.